2012
DOI: 10.1118/1.4730287
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of imaging performance in differential phase contrast CT compared with the conventional CT: Spectrum of noise equivalent quanta NEQ( k )

Abstract: Purpose: Differential phase contrast CT (DPC-CT) is emerging as a new technology to improve the contrast sensitivity of conventional attenuation-based CT. The noise equivalent quanta as a function over spatial frequency, i.e., the spectrum of noise equivalent quanta NEQ(k), is a decisive indicator of the signal and noise transfer properties of an imaging system. In this work, we derive the functional form of NEQ(k) in DPC-CT. Via system modeling, analysis, and computer simulation, we evaluate and verify the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…(6), into Eq. (8). Once Q m (0)/Q m (1) is computed for a given interferometer setup, the gradients ∂ρ e, p (x, y)/∂x of sample's projected electron densities can be found from the measured polychromatic fringe phase shift φ m,Poly (x, y) as follows:…”
Section: First Order Approximationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(6), into Eq. (8). Once Q m (0)/Q m (1) is computed for a given interferometer setup, the gradients ∂ρ e, p (x, y)/∂x of sample's projected electron densities can be found from the measured polychromatic fringe phase shift φ m,Poly (x, y) as follows:…”
Section: First Order Approximationsmentioning
confidence: 99%
“…(3). Repeating this retrieval procedure for all angular projections, one will be able to compute the quantitative volumetric distribution of sample's electron densities by using the tomographic reconstruction method [6][7][8]20]. Hence the retrieval of fringe phase shifts is a task crucial to the grating based phase contrast imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional advantage of GI is the comparatively low coherence requirement, which allows not only the use of synchrotron sources but, utilizing a third grating, also of standard laboratory X-ray tubes (Pfeiffer et al, 2006). This makes GI of special interest for medical applications and in recent years a lot of effort has been put into making this technique available for clinical applications (Stampanoni et al, 2011;Tang et al, 2012;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, theoretical investigations with numerical simulations have been performed to study the NEQ of an idealized DPC-CT system. 39,40 These studies concluded that the total NEQ of a DPC-CT system could be either double 39 or identical to 40 that of the corresponding ACT system. However, a modified definition of NEQ was introduced for DPC-CT in Refs.…”
Section: Introductionmentioning
confidence: 99%